The development and intellectual structure of continuous auditing research✩. Issue 1 (12th August 2014) - Chiu, Victoria; Liu, Qi; Vasarhelyi, Miklos A.
Abstract : The advances and continuous development of technology have been identified as significant influences on the accounting profession (AICPA, 1998). In the last twenty years, both academia and the accounting profession have been giving much attention to the demand and opportunity for audits to be performed automatically, continuously and in nearly real time. This paper presents a comprehensive review of continuous auditing research by providing an overview of the emergence and growth of the continuous auditing literature and classifying the extant continuous auditing research on the basis of four research characteristics indicated by a newly developed research taxonomy.